Determining fundamental breach in international sale of goods: taming the unruly horse? - Hamid, Abdul Ghafur@Khin Maung Sein; Eishan Jan, Mohammad Naqib; Khairunnasriah, Abdul Salam (2016)
The remedial system is the most distinctive feature of the United Nations Convention on Contracts for the International Sale of Goods (CISG) 1980 and the remedy of ‘avoidance’ is not available for every breach of contract but only for a fundamental one. Despite the fact that the term is specifically defined in Article 25, many commentators are of the view that the meaning of “fundamental breach” is vague and uncertain. The present paper analyzes the dual elements of ‘fundamental breach,’ namely, substantial detriment and unforeseeability, on the basis of interpretative tools of the Convention, legislative history, and an in-depth survey of judicial decisions on fundamental breach from various countries. The paper finds that it is too drastic to say that the meaning of fundamental breach as defined in CISG is vague and that on the contrary the meaning is clearly instructive and can be refined through judicial interpretation. The paper concludes that though it will take time for case law to completely cover most of the possible situations of fundamental breach, it is pretty clear at this stage that a number of basic principles for the determination of fundamental breach are well settled and established.